Marketing Assistance and Herbal Products Market Expansion of Paguyuban Jamu Gendong Desa Ngablak - Safii, Azis; Rahayu, Susilowati; Anom, Latifah (IMPOWERMENT SOCIETY, 2022)
The Corona pandemic has occurred globally by closing access to residential areas by residents from immigrants and foreign traders. The protection of the area has caused almost all business activities of members of Paguyuban Jamu Gendong Desa Ngablak to stop because they cannot sell directly to consumers. The MSME empowerment program for Herbal Medicine in Ngablak Village aims to provide sales solutions for business actors without direct contact with consumers. Social media and e-commerce-based marketing assistance aim to increase the sales turnover of herbal medicine through direct orders for herbal products from Ngablak Village herbal producers by consumers. Meanwhile, the development of ready-to-brewed herbal products is expected to provide a more comprehensive market share with herbal products with a longer shelf life.